Fabry Disease Beyond Storage: The Role of Inflammation in Disease Progression - Biddeci, Giuseppa; Spinelli, Gaetano; Colomba, Paolo; Duro, Giovanni; Giacalone, Irene; Di Blasi, Francesco (International journal of molecular sciences, 2025)
Fabry disease (FD) is a rare X-linked lysosomal storage disorder caused by mutations in the GLA gene, resulting in a deficient activity of the enzyme α-galactosidase A (α-Gal A). This deficiency leads to the progressive accumulation of globotriaosylceramide (Gb3) and its deacylated form, globotriaosylsphingosine (Lyso-Gb3), in various tissues, contributing to a broad spectrum of clinical manifestations. Recent evidence highlights the crucial role of inflammation in the pathophysiology of FD, influencing disease progression and clinical outcomes. This review provides a comprehensive overview of the relationship between inflammation and FD, with a particular focus on the impact of inflammatory processes on disease progression and complications.